KAJIAN KOMPARATIF AKTIVITAS ANTIOKSIDAN FORMULA PENGAWET ALAMI EKSTRAK KECOMBRANG (Nicolaia speciosa Horan) DAN POLA PEMISAHAN KROMATOGRAFIS EKSTRAK BAGIAN-BAGIAN TANAMAN KECOMBRANG - Pristiadi, Pristiadi (Journal of Inovation and Technology of Agroindustry, 2012)
KAJIAN KOMPARATIF AKTIVITAS ANTIOKSIDAN FORMULA PENGAWET ALAMI EKSTRAK KECOMBRANG (Nicolaia speciosa Horan) DAN POLA PEMISAHANKROMATOGRAFIS EKSTRAK BAGIAN-BAGIANTANAMAN KECOMBRANGOleh : PristiadiProgram Pascasarjana, Universitas Jenderal Soedirman, PurwokertoAbstractKecombrang (Nicolaia speciosa Horan) contains alkaloid compounds, saponin, tannin, phenolic, flavonoid,triterpenoid, steroid and glycoside which act as antimicrobial and antioxidant. Utilization kecombrang in the form of fresh or extract is easy to loss of volatile components, so that need to be formulated with the addition of fillers, stabilizers, NaCl and pH treatment. Formula that has antimicrobial activity investigated as total phenolic content and antioxidant activities. Tests performed on thin-layer chromatography of fruit extracts, rhizome extracts, stem extracts and flower extracts to get the chromatography pattern and Rf values. Experiment of eight formulas of kecombrang extracts have the highest measurement results obtaining on the formula F1 (15% fillers, 1% stabilizers,2.5% NaCl and pH 4) with total phenolic content of 323.25 mg/100 g and 58.49% antioxidant activity. The relationship between total phenolic content with antioxidant activity of formulas of kecombrang extracts obtained correlation value r = 0.92 this shows that 92% of the total phenolic effect on antioxidant activity. It shown the result of thin layer chromatography tests with GF254 stationary phase and ethyl acetate - formic acid - glacialacetic acid - water eluent (100:11:11:26) on stem and flower extracts (Rf 0.15; 0.54; 0.94), fruit extracts (Rf 0.09; 0.94) and rhizome extracts (Rf 0.15). The similarity of Rf values on kecombrang extracts shown similar compounds contained in it.Keywords : total phenolic, antioxidant activity